2013
DOI: 10.1038/srep01299
|View full text |Cite
|
Sign up to set email alerts
|

Middle-redox potential laccase from Ganoderma sp.: its application in improvement of feed for monogastric animals

Abstract: The variables influencing laccase production by white-rot fungus Ganoderma sp. rckk-02 were optimized employing response surface methodology. Malt extract (6.0% w/v), lignin (0.5% w/v) and pH (5.5) were found to be the most significant factors for enhanced laccase production by 7 fold (226.0 U/ml) as compared to unoptimized growth conditions (32.0 U/ml). The N-terminal sequence of laccase revealed its distinct amino acid profile (S- I- R- N- S- G), which suggested it as a novel enzyme. The Far-UV CD spectrum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 30 publications
3
34
1
Order By: Relevance
“…The effect of detergents on immobilized laccase was not reported earlier. In contrast to earlier studies reported on free enzymes (Laufer et al 2006;Sharma et al 2013), SDS decreased the enzymatic activity of immobilized laccase at concentrations higher than 2 mM. This study for the first time demonstrates the effect of detergents on immobilized laccase.…”
Section: Effect Of Detergentscontrasting
confidence: 52%
See 2 more Smart Citations
“…The effect of detergents on immobilized laccase was not reported earlier. In contrast to earlier studies reported on free enzymes (Laufer et al 2006;Sharma et al 2013), SDS decreased the enzymatic activity of immobilized laccase at concentrations higher than 2 mM. This study for the first time demonstrates the effect of detergents on immobilized laccase.…”
Section: Effect Of Detergentscontrasting
confidence: 52%
“…Recent study on purified laccase from Ganoderma sp. has shown maximum inhibition of laccase with CoCl 2 and HgCl 2 and stability in presence of CaCl 2 , MnSO 4 , FeCl 3 , ZnSO 4 and BaCl 2 (0.5-3 mM) with a significant inhibition only at 10 mM of the metal ions (Sharma et al 2013). However, the effect of metal ions on immobilized laccase was not reported earlier.…”
Section: Effect Of Metal Ionsmentioning
confidence: 59%
See 1 more Smart Citation
“…Recent, whole genome sequence of G. lucidum has revealed complete set of ligninolytic peroxidases, laccases and cellobiose dehydrogenases, which makes it excellent model for ligninolytic enzymatic studies [2]. Earlier, Ganoderma has been reported with different lignin modifying enzymes, such as, manganese-dependent peroxidase (MnP) and laccase [3,4]. Laccases (p-diphenol: dioxygen oxidoreductase; EC 1.10.3.2) are polyphenol oxidases that catalyze the oxidation of phenolic compounds with a concomitant reduction of oxygen to water [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these lignocellulose-rich substrates, which can be made available by WRF metabolism, is limited in ruminant nutrition (Sarnklong et al, 2010;Millati et al, 2011). As a result, limited research has been conducted concerning the use of lignocellulose-rich substrates in monogastric animal diets (Shrivastava et al, 2011;Sharma et al, 2013;Shrivastava et al, 2014). Although some studies have evaluated lignocellulose-rich substrate use in order to increase the nutritional value of different agroindustrial wastes, few have examined the effects of WRF-hydrolysed ingredients on production traits and rabbit meat quality (Brozzoli et al, 2010;Shrivastava et al, 2011;Isikhuemhen et al, 2012;Tanemura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%